AB0467 Rapid achievement of remission with certolizumab pegol was maintained for one year: interim results from fast, a german non-interventional study in rheumatoid arthritis real life patients. (23rd January 2014) - Burmester, G.; Müller-Ladner, U.; Nüsslein, H.; von Hinuber, U.; Edelmann, E.; Detert, J.; Höhle, M.; Richter, C.; Klopsch, T.; Kumke, T.; Fricke, D.
Abstract : Background: Certolizumab pegol (CZP) demonstrated a fast response and acceptable safety profile in clinical studies in rheumatoid arthritis (RA). 1-3 Objectives: To assess use of CZP in daily clinical practice in Germany. Methods: The efficacy and tolerability of CZP (approved dosage: 400 mg at Weeks [Wks] 0, 2, and 4, then 200 mg every other Wk) is being assessed among 1068 patients (pts) with RA from 160 sites in the ongoing FαsT trial. Primary endpoint is DAS28(CRP) remission at Wk 104. At the cut-off date for this interim analysis (July 2011) 665 pts were enrolled. Wk 12 efficacy and safety data is reported in 160 pts with an available DAS28(CRP) value at baseline (BL) and Wk 12 (±1). Wk 52 (±8) efficacy is reported in 56 pts who completed up to 1 year and have non-missing observations (NMO). Results: Of the 160 pts, 73% were female, mean age 54 years (yrs). At BL, 81% pts were RF positive and 79% ACPA positive. 50%/16% had received prior TNF inhibitors/other biologics, 90% had prior synthetic DMARDs. Mean RA duration was 10.7 yrs; mean CRP was 19.4 mg/L. Mean (SD) BL scores were: TJC 9.5 (6.8), SJC 7.6 (5.9), CDAI 29.9 (12.6), DAS28(CRP) 4.9 (1.0), DAS28(ESR) 5.4 (1.1) HAQ-DI 1.3 (0.7). Of the 160 pts, mean change from BL was -1.42 (1.3) in DAS28(CRP) at Wk 12 and 30.6%/16.3% were in DAS28(CRP) remission (REM)/low disease activity (LDA). Disposition of the 160 pts at Wk 52 is divided into pts with available DAS28(CRP) values (36.3%), pts who did not reach Wk 52 yet (38.3%) and pts who discontinued between Wk 12 and 52 (25%). 56 pts with NMO at Wk 52 reported mean (SD) changes from BL in DAS28(CRP) of -1.61 (1.1) at Wk 12 and -1.77 (1.3) at Wk 52. Of these 56 pts, at Wk 12 33.9%/28.6% and at Wk 52 44.6%/19.6% were in REM/LDA. The sum of the categories LDA/REM was similar (∼60%) at Wk 12 and 52 (Figure). Incidence rate (IR) of adverse events (AE) was 90 cases/100 pt-yrs (38 infections) and the IR of serious AE was 10.5 cases/100 pt-yrs. No deaths or cases of TB were reported. Conclusions: In the FαsT non-interventional study, "real-life" RA pts treated with CZP achieved a fast reduction of disease activity by Wk12 which further improved for pts with available DAS28(CRP) values at Wk 52. Incidence and severity of AE was consistent with previous CZP experience and in line with the summary of product characteristics. References: Arthritis Rheum 2008;58:3319–3329. Ann Rheum Dis 2009;68:797–804. Ann Rheum Dis 2009;68:805–811. Disclosure of Interest: G. Burmester Grant/Research support from: UCB Pharma, Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, U. Müller-Ladner Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, H. Nüsslein Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, U. von Hinuber Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, E. Edelmann Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, J. Detert Consultant for: UCB Pharma, M. Höhle: None Declared, C. Richter Consultant for: UCB Pharma, Speakers Bureau: UCB Pharma, T. Klopsch: None Declared, T. Kumke Employee of: UCB Pharma, D. Fricke Employee of: UCB Pharma